(untitled) (Research, Society and Development, 2021)
Arachis Hypogaea L. has a strong economic importance in Brazil, being used in the in natura form and in the production of its derivatives as oils, pastes and bullets. The municipality of Petrolândia in the state of Pernambuco, located in the semi-arid region of the Northeast, presents climatic characteristics conducive to the good development of the crop with temperature in the range of 28 to 32 ºC. The objective of this work was to analyze the growth of peanut crop, cultivar BR1, for different soil preparation systems as a function of the water slides, and the influence of these parameters on productivity. The efficient use of water and the cost benefit of production in the region were evaluated. The work was done using the experimental design of randomized blocks and the plots were arranged in strip in 4 replications, with the preparation of soil arranged in the main plot and irrigation slides in the secondary plots, thus distributed. Soil preparation was done using Disk Plow, Harrow, Scarifier and Leveling Grate. The irrigation slides were used considering 50, 75, 100 and 125% of the water requirement of the culture. The consecutive increase of the irrigation slides showed an increase in productivity. Soil preparation systems did not show a significant increase in production. The higher efficiency of water use was observed with the 50% slide. The best cost benefit was identified in the preparation with scarifier + leveler with the 100% ETc blade.